Vancomycin Induced Nephrotoxicity: A Case Report - Santoshini Naveen; Peter Jensen (International Healthcare Research Journal, 2022)
Nephrotoxicity associated with vancomycin is a commonly feared and mainly preventable adverse effect. Non-severe cases of vancomycin nephrotoxicity resolve upon discontinuation of the medication. We present the case of a 45-year-old man who developed renal dysfunction following vancomycin antibiotic therapy as a result of lack of dose adaptation to measured serum nadirs.